Measurement with persons : theory, methods, and implementation areas - Berglund, Birgitta (New York : Psychology Press, 2012)
'Measurements with persons are those in which human perception and interpretation are used for measuring complex, holistic quantities and qualities. Providing reproducible measurement of parameters for things such as pleasure and pain has important implications in evaluating products, services, and conditions. Progress in this area requires the interlinking of related developments across a variety of disciplines, embracing the physical, biological, psychological, and social sciences. Physicists and psychologists have disagreed strongly on the meaning of measurement and the possibility of'measuring' sensory events. This led to parallel developments in measurement science within the two separate camps. Both went on to generate remarkable results, but the lack of communication between them prevented coherent and interactive progress. This book's aim is to cover the topic of measurement with persons by multi- and interdisciplinary approaches, integrating the complementary aspects of general theory, measurement methods, instrumentation and modeling with the fields of psychophysics and general psychology, measurement theory, metrology and instrumentation, neurophysiology, engineering, biology, and chemistry. In the first part, generic theoretical and methodological issues are treated, including the conceptual basis of measurement in the various fields involved, the development of formal, representational and probabilistic, theories, the approach to experimentation and the theories, models and methods for multifaceted problems. In the second part, several implementation areas are presented, including sound, visual and skin perception, functional brain imagining, body language and emotions, and, finally, the use of measurements in decision making'--
Includes bibliographical references and indexes.
Keywords: Perception -- Mathematical models; Senses and sensation -- Mathematical models; Human information processing -- Mathematical models